2014
DOI: 10.1177/0023677214553320
|View full text |Cite
|
Sign up to set email alerts
|

Aspen shaving versus chip bedding: effects on breeding and behavior

Abstract: The choice of laboratory cage bedding material is often based on both practical and husbandry issues, whereas behavioral outcomes rarely appear to be considered. It has been noted that a breeding success difference appears to be associated with the differential use of aspen chip and aspen shaving bedding in our facility; therefore, we sought to analyze breeding records maintained over a 20-month period. In fact, in all four mouse strains analyzed, shaving bedding was associated with a significant increase in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(53 reference statements)
0
11
1
Order By: Relevance
“…A wide variety of bedding types continue to be used to house mice in these boxes. The different bedding types can affect breeding ( Iturrian and Fink, 1968 ; Jackson et al, 2015 ; Tanaka et al, 2014 ), overall health ( Becker et al, 2010 ; Ferrecchia et al, 2014 ; Horn et al, 2012 ; Potgieter and Wilke, 1996 ) or metabolism. This can lead to a wide variety of disorders, including cancer ( Jacobs and Dieter, 1978 ; Li et al, 2009 ; Nielsen et al, 1986 ; Schoental, 1974 ; Torronen et al, 1989 ; Vesell, 1967 ; Vlahakis, 1977 ).…”
Section: Environmental Carcinogensmentioning
confidence: 99%
“…A wide variety of bedding types continue to be used to house mice in these boxes. The different bedding types can affect breeding ( Iturrian and Fink, 1968 ; Jackson et al, 2015 ; Tanaka et al, 2014 ), overall health ( Becker et al, 2010 ; Ferrecchia et al, 2014 ; Horn et al, 2012 ; Potgieter and Wilke, 1996 ) or metabolism. This can lead to a wide variety of disorders, including cancer ( Jacobs and Dieter, 1978 ; Li et al, 2009 ; Nielsen et al, 1986 ; Schoental, 1974 ; Torronen et al, 1989 ; Vesell, 1967 ; Vlahakis, 1977 ).…”
Section: Environmental Carcinogensmentioning
confidence: 99%
“…When designing studies that use animal models, it has been recognized that the results are more translatable to human disease when the subjects are healthy with minimal stressors [1][2][3][4][5][6] . But, not all stress is bad, so it is critical that evaluations of animal well-being differentiate between distress (that which results in decreases in animal well-being as the animal is unable to cope or adapt) and eustress (stressors which enhance the functioning of the animal) 7,8 .…”
mentioning
confidence: 99%
“…It has long been known that different bedding materials can affect the wellbeing and sexual behavior of mice 25,28,48,55 , but the potential effects on the evoked and non-evoked somatosensory behavior assays have been little studied. Through the combination of a variety of evoked and non-evoked assays, and acute and chronic tissue inflammation, we have shown that the bedding type can markedly affect animal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The animal facility at our institute typically uses an Aspen wood chip bedding called Sani-Chips® (Fig 1A), which when touched feels somewhat prickly with sharp edges, even though the wood pieces are small. The Aspen chips are dried to about 8% moisture content and then screened to the specifications which include a size range from 8 to 20 mesh of the National Institute of Health 28 . The Aspen Sani Chips® we use come from P.J.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation